Scripture and Its Interpretation A Global, Ecumenical Introduction to the Bible - Gorman, Michael J. 1955- (Grand Rapids Baker Academic, 2017)
Top-notch biblical scholars from around the world and from various Christian traditions offer a fulsome yet readable introduction to the Bible and its interpretation.
Intro -- Title Page -- Copyright Page -- Endorsements -- Dedication -- Contents -- Illustrations -- Acknowledgments -- Contributors -- Abbreviations -- Introduction -- Part 1: The Bible -- 1. The Bible: A Book, a Library, a Story, an Invitation -- 2. The Setting: Biblical Geography, History, and Archaeology -- 3. The Scriptures of Israel (The Christian Old Testament) -- 4. The Writings of the New Covenant (The New Testament) -- 5. Significant Noncanonical Writings -- 6. From Books to Library: The Formation of the Biblical Canons -- 7. From There to Here: The Transmission and Translation of the Bible -- Part 2: The Interpretation of the Bible in Various Traditions and Cultures -- 8. The Reception of the Bible and Its Significance -- 9. Premodern Interpretation of the Bible -- 10. Modern and Postmodern Methods of Biblical Interpretation -- 11. Theological Interpretation of the Bible -- 12. Protestant Biblical Interpretation -- 13. Roman Catholic Biblical Interpretation -- 14. Orthodox Interpretation of Scripture -- 15. Pentecostal Biblical Interpretation / Spirit Hermeneutics -- 16. African Biblical Interpretation -- 17. African American Biblical Interpretation -- 18. Latino/Latina Biblical Interpretation -- 19. Asian and Asian American Biblical Interpretation -- Part 3: The Bible and Contemporary Christian Existence -- 20. The Bible and Spirituality -- 21. Scripture and Christian Ethics: Embodying Pentecost -- 22. The Bible and Politics -- 23. Scripture and Christian Community -- 24. The Bible and Christian Mission -- Glossary -- Scripture Index -- Subject and Author Index -- Back Cover.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books